The Zombie Phenomenon in Banking and Business: a Comparative Analysis and the Origin of the Institutional Problem - Ihor Hurnyak; Aleksandra Kordonska (Comparative Economic Research. Central and Eastern Europe, 2019)
The research presents an investigation of the zombie phenomenon in banking and business. The main goals are as follows: to reveal the consequences of the threatening dynamics of nonperforming loans for the states of Central and Eastern Europe, Western Europe, the group of former USSR states, and Latin America; to demonstrate the zombie business phenomenon in the case of Ukraine and disclose a new form of zombie business on the basis of different tools with exception of banking loans. The authors believe the solution to the zombie banks problem will not be found in the growth of government influence or control but in the restructuring of the banking system based on a decentralized but strongly controlled bottom-up model. The ineffectiveness of the institutional system also generates various forms of zombie business. The case of Ukraine is the best illustration of applying the tools, that are used in zombie business, with the exception of banking loans. The article helps to understand the influence of nonperforming loans on the economy and the perspectives for banking system formation in the light of the institutional aspect and interinstitutional interactions with the active participation of NPLs.
Keywords: D02; F34; 330; bank system; banking; zombie banks; zombie business; nonperforming loans; institutional theory